Методи вилучення невідомих за допомогою операцій проектування - Ostapenko, V. V.; Finin, G. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
In the paper the connection between operation of projection and methods of elimination of unknowns is investigated. Separately, considered is a method of sequential elimination of one unknown, and a method of elimination of group of unknowns. Special attention is given to methods of elimination of unknowns from the system of inequalities with a graph structure.